Oyster mushroom cultivation for resource poor tribal farmers - Mooventhan, P; Kumar, Jagdish; Dixit, Anil; Sharma, K C; Sivalingam, N; Gupta, Amit Kumar; Singh, Uttam; Singh, S R K; Venkatesan, P; Kaushal, Pankaj (Indian Horticulture, 2019)
Oyster mushroom cultivation with four model mushroom production units was introduced under the Farmer FIRST Programme among the tribal people in the Kasdol block of Chhattisgarh to help the farm women and rural youth in the area to have a sustainable livelihood. Hands on training on mushroom production was provided with the help of IGKV, Raipur. The paddy straw waste after the harvest was used for mushroom cultivation which requires huge quantity of straw and thereby prevents leaving and burning practice prevalent among the farmers of the region by making effective use of the waste. The farmers obtained maximum production by harvesting the mushroom in all the four mushroom units.